2023
DOI: 10.1177/00145858231166913
|View full text |Cite
|
Sign up to set email alerts
|

Join or die: How deontological moral intuitions complicate cooperation amid the COVID-19 pandemic

Abstract: Tackling COVID-19 requires universal collective action: everyone must play their part to reduce the spread of the virus and quell the pandemic. Yet, some people obstinately refuse to cooperate, irrespective of the consequences for themselves and others. In this note, I illustrate a key element of human psychology that hampers cooperation amid the pandemic: deontological moral intuitions. Deontological morality prescribes that moral taboos must be followed no matter the consequences. This means that people who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…greater political involvement), morally convicted attitudes appear to have "a dark side as well" (Skitka et al, 2005: 914). Indeed, previous studies have found that morally convicted attitudes arouse strong negative feelings, inhibit compromise, engender hostile opinions and inspire punitive actions toward morally distant others (Del Ponte, 2023;Ryan, 2014Ryan, , 2017Skitka et al, 2005).…”
Section: The Moral Dimension Of Sovereign Debtmentioning
confidence: 99%
“…greater political involvement), morally convicted attitudes appear to have "a dark side as well" (Skitka et al, 2005: 914). Indeed, previous studies have found that morally convicted attitudes arouse strong negative feelings, inhibit compromise, engender hostile opinions and inspire punitive actions toward morally distant others (Del Ponte, 2023;Ryan, 2014Ryan, , 2017Skitka et al, 2005).…”
Section: The Moral Dimension Of Sovereign Debtmentioning
confidence: 99%